Engagement in Indonesian Police Interrogation: An Appraisal Analysis of Interpersonal Strategies - Ramadani, Ramadani; Saifullah, Aceng Ruhendi; Gunawan, Wawan (Journal of Languages and Language Teaching, 2025)
This study explored the use of evaluative language in the speech of investigators and suspects during police interrogations at a district police department in Indonesia. The study aimed to analyze how interpersonal strategies were realized by the police as interrogators and suspects during interrogations. To achieve these objectives, the research applied appraisal theory within the framework of Systemic Functional Linguistics (SFL) to identify and examine the language of evaluation. The data for the study were derived from conversations between police interrogators and suspects. The analysis involved segmenting the interrogation texts into units of utterances. There were 1320 utterances of 5 suspects analyzed in this study. These utterances were then systematically categorized based on the appraisal system's categories. Specifically, the analysis focused on the appraisal system's engagement dimension, examining the realization of monoglosss and heterogloss. The findings revealed that the expression of engagement was predominantly characterized by heterogloss, primarily conveyed by the interrogator. The findings indicated that during the interrogation process, the police increased control, reduced space for the suspect's perspective, introduced bias in information gathering, and emphasized a clearer power dynamic, which can impact the validity and ethics of the interrogation. The findings contributed to forensic linguistics practice to create opportunities for more cooperative interactions, thereby enhancing the effectiveness of information elicitation.